Ten years of harmonic and flicker control by IEC normalised measurements in Buenos Aires distribution system - Issouribehere, Pedro (2007)
The electricity distribution service in Buenos Aires – Argentina – was privatised in the early nineties. This service is provided by three different Utilities and the control is carried out by a Regulatory Agency (ENRE). The IITREE of La Plata University provides technical assistance to the Regulatory Agency. Since the beginning of the privatisation, extensive Monitoring Programs regarding Power Quality have been carried out. The control of harmonics and flicker, which is detailed in [1] and [2], began in 1997. For this reason, a decade of permanent control has been achieved so far. The three Utilities – called A, B and C in the present paper – perform 45 weekly measurements per month. Therefore, several thousands of measurements have been collected. By the time this control began, the existing limits in IEC standards for both harmonics and flicker were adopted in order to obtain a starting point for the local regulation. In addition, the equipment employed to perform the measurements also meets IEC standards [3] [4]. In every site in which the limits established for harmonics and flicker in voltage quality are exceeded, the Utility is penalised. The fine, applied only to this site, continues until a new measurement proves that the problem has been solved. The aim of the article is to show the results obtained over the first 10 years of control. The carried out studies mainly consisted of processing the data gathered during the whole decade with the purpose of obtaining: disturbance trends over the years, comparisons of the levels measured in different Utilities as well as disturbance behaviours throughout the day. In addition to this, the degree of fulfilment achieved by the Utilities was also assessed. In the next sections the results obtained in the control of both types of disturbances are presented.